A fixed-dose, dose–response study of ropinirole prolonged release in early stage Parkinson's disease. (February 2017) - Zesiewicz, Theresa A; Chriscoe, Stephen; Jimenez, Theresa; Upward, James; VanMeter, Susan
Aim: This Phase IV, double-blind, randomized, parallel-group study characterized the dose–response and tolerability of fixed doses of ropinirole prolonged release (PR).Patients & methods: Subjects with early Parkinson's disease (PD) received placebo or ropinirole PR 2, 4, 8, 12 or 24 mg once daily, up-titrated to randomized or highest tolerated dose, maintained for 4 weeks.Results: The primary end point was not met (change from baseline in Unified PD Rating Scale motor score). However, because the data were not normally distributed, prespecified nonparametric analysis of covariance suggested ropinirole PR (8 and 12 mg/day) was effective in treating motor symptoms. The adverse event profile was consistent with the known safety profile of ropinirole PR. There was no impulse control disorder reported. Although a higher than previously reported rate of sudden onset of sleep events was reported, these were not dose dependent and were likely to have been influenced by the method of data collection.Conclusion: The adverse event profile was consistent with the known safety profile of ropinirole PR and ropinirole PR (8 or 12 mg/day) improved motor symptoms of early PD.